Larval morphology of Nicrophorus (Nicrophorus) nepalensis Hope (Coleoptera: Silphidae: Nicrophorinae) - Šípková, Hana; Růžička, Jan (Zootaxa, 2020)
Larval morphology of all three instars of Nicrophorus (Nicrophorus) nepalensis Hope, 1831 (Coleoptera: Silphidae: Nicrophorinae) is described and illustrated, based on reared larvae. The eastern Palaearctic and Oriental N. (N.) nepalensis is similar to the western Palaearctic N. (N.) humator (Gleditsch, 1767) in a number of larval characters. This is congruent with recent classification of the genus Nicrophorus Fabricius, 1775 by Sikes, who suggested a close phylogenetic affinity of the N. nepalensis species group (with 16 species) with the N. humator species group (2 species). The generic description of larvae of Nicrophorus Fabricius, 1775 is expanded, based on detailed SEM observation.